Isolation and characterization of bacteriophage from catfish (Clarias batrachus) - Nurul Natasya Azhari. (2015)
This project was carried out to isolate, purify and characterize bacteriophage isolated from catfish (Clarias batrachus) which is a freshwater fish. From this project, fve unknown bacteria were isolated from the catfish originated from Sungai Pelek, Sepang. The bacteria were labelled as B1, B2, B3, B4 and B5 and five other known bacteria (Pseudomonas aeruginosa, Klebsiella pneumonia, Escherichia coli, Staphylococcus aureus and Bacillus cereus) were obtained from the stock provided by the Microbiology department, UPM. All ten species of bacteria were used for the isolation but only bacteria B5 and Pseudomonas aeruginosa were infected by the bacteriophage. The bacteriophages were labelled as ØB5 and ØPa. The host bacteria of the phage were identified by gram staining and biochemical tests. Based on the gram staining, both of the bacteria were gram-negative with rod shape. Then the isolated bacteriophage was characterized based on their genomic, biology and physical characracteristics. At the end of the study the isolated bacteriophage were classified as DNA containing bacteriophages with lytic life cycle. The bacteriophages could be used in the phage therapy against the bacterial contamination.